Rancang Bangun Rekam Medis Elektronik Rawat Jalan Berbasis Web Mobile View di Puskesmas I Melaya - Ni Kadek Sri Windariyasih; Rai Riska Resty Wasita; Gerson Feoh (Malahayati Nursing Journal, 2023)
ABSTRACT The still manual management of medical records at Puskesmas I Melaya resulted in medical records not being found, caused by the medical record storage racks being in three different places and not being kept safe. This causes the medical record search time to exceed the standard procedure. With the above problems, a web-based mobile view-based electronic medical record was designed to facilitate the search for medical records and their management in a computerized manner. The development of a web-based mobile view electronic medical record system uses the System Development Life Cycle method. Sample determination was determined by probability sampling technique with simple random sampling with 19 samples. Testing this information system uses black box testing. Tested its usability using the USE Questionnaire with 30 questions. Usability testing with the USE Questionnaire proved 81.40% results with an "excellent" classification, which was shown to speed up the patient's medical record search time from 12 minutes to 0.47 minutes. Keywords: Electronic Medical Records, Web Mobile View, Puskesmas I Melaya  ABSTRAK Masih manualnya pengelolaan rekam medis di Puskesmas I Melaya  mengakibatkan terjadi rekam medis tidak ditemukan, disebabkan oleh rak penyimpanan rekam medis tersebut berada di tiga tempat yang berbeda dan kurang terjaga keamanannya. Dengan ini menyebabkan waktu pencarian rekam medis melebihi standar prosedur. Dengan masalah diatas dibuat rancang bangun rekam medis elektronik berbasis web mobile view untuk mempermudah pencarian rekam medis dan pengelolaannya secara terkomputerisasi. Pengembangan sistem rekam medis elektronik berbasis web mobile view ini menggunakan metode System Development Life Cycle. Determinasi sampel di tentukan dengan teknik probability sampling dengan simple random sampling dengan 19 sampel. Pengujian sistem informasi ini menggunakan black box testing. Diuji usability-nya menggunakan USE Questionnaire dengan 30 pertanyaan. Pengujian usability dengan USE Questionnaire membuktikan hasil 81,40% dengan klasifikasi “sangat baik”, yang terbukti mempercepat waktu pencarian rekam medis pasien dari 12 menit menjadi 0,47 menit. Kata Kunci: Rekam Medis Elektronik, Web Mobile View, Puskesmas I Melaya.